2007
DOI: 10.1007/s10722-007-9263-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of sweet and sour cherry cultivars in a germplasm bank at Portugal

Abstract: Nine sweet cherry and eight sour cherry varieties located in a germplasm bank at Fundão, Portugal, were studied from the viewpoint of characterization. Most of them were autochthonous cultivars that have a high risk of extinction since at the present they are markedly minor varieties. Morphological characteristics were evaluated in different organs: crown and trunk of the trees, leaves, flowers and fruits, over a three consecutive years period. Statistical analyses were carried out in order to detect similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 4 publications
(1 reference statement)
4
32
0
Order By: Relevance
“…The first group of this cluster included accessions of four species (P. mahaleb and sweet, sour and duke cherries) and the second group included accessions of mazzard, because mazzard had higher height (up to 35 m), higher trunk diameter, higher internode length, higher leaf length and width (16 and 8 cm, respectively), higher petiole length and higher flower peduncle length than the accessions of the first group. The first group of the first cluster was also divided into two subgroups, the first subgroup included accessions of P. mahaleb and the second subgroup Rodrigues et al (2008) reported that dendrogram obtained from morphological characteristics clearly separated sweet cherries from sour cherries. Also, Perez-Sanchez et al (2008) suggested that dendrogram gained from morphological parameters clearly showed the relationships among the cultivars of sweet, sour and duke cherries.…”
Section: Cluster Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The first group of this cluster included accessions of four species (P. mahaleb and sweet, sour and duke cherries) and the second group included accessions of mazzard, because mazzard had higher height (up to 35 m), higher trunk diameter, higher internode length, higher leaf length and width (16 and 8 cm, respectively), higher petiole length and higher flower peduncle length than the accessions of the first group. The first group of the first cluster was also divided into two subgroups, the first subgroup included accessions of P. mahaleb and the second subgroup Rodrigues et al (2008) reported that dendrogram obtained from morphological characteristics clearly separated sweet cherries from sour cherries. Also, Perez-Sanchez et al (2008) suggested that dendrogram gained from morphological parameters clearly showed the relationships among the cultivars of sweet, sour and duke cherries.…”
Section: Cluster Analysismentioning
confidence: 99%
“…Several morphological characterization studies have been carried on the Cerasus species and important results have been obtained, such as on sweet cherry (Christensen 1970), ground cherry , sour cherry (Krahl et al 1991;Rodrigues et al 2008;Rakonjac et al 2010), duke cherry (Tavaud et al 2004), mahaleb (Ganji Moghadam and Khalighi 2007) and some Cerasus genotypes (Shahi-Gharahlar et al 2010).…”
mentioning
confidence: 99%
“…PCA was used to identify the most significant variables in the data set. PCA has been used until now to evaluate germplasm of different Prunus species, including peach (Perez et al, 1993;Esti et al, 1997;Wu et al, 2003;, apricot (Badenes et al, 1998;Ruiz and Egea, 2008;Yılmaz et al, 2012), mahaleb Khalighi, 2006, 2007), cherry plum (Horvath et al, 2008;Sedaghathoor et al, 2009;Aran et al, 2012), sour cherry (Krahl et al, 1991;Onal, 2002;Rakonjac et al, 2010), cherry (Hillig and Iezzoni, 1988;Hjalmarsson and Ortiz, 2000;Beyer et al, 2002, Rodrigues et al, 2008Perez Sanchez et al, 2008;Lacis et al, 2009, and Prunus incana (Nazari et al, 2012). Morphological characterization is necessary for germplasm description and classification, and statistical methods such as PCA are useful tools for screening the accessions of a collection (Cantini et al, 1999;Badenes et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Most of them were autochthonous cultivars that had a high risk of extinction since at the present they are markedly minor varieties. Therefore, conservation of the autochthonous cultivars in the future is highly recommended (Rodrigues et al, 2008).…”
Section: Introductionmentioning
confidence: 99%